2023
DOI: 10.1038/s41598-023-36125-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of cancer-associated fibroblasts-related subtypes and prognostic index for prostate cancer through single-cell and bulk RNA transcriptome

Abstract: Current evidence indicate that cancer-associated fibroblasts (CAFs) play an important role in prostate cancer (PCa) development and progression. In this study, we identified CAF-related molecular subtypes and prognostic index for PCa patients undergoing radical prostatectomy through integrating single-cell and bulk RNA sequencing data. We completed analyses using software R 3.6.3 and its suitable packages. Through single-cell and bulk RNA sequencing analysis, NDRG2, TSPAN1, PTN, APOE, OR51E2, P4HB, STEAP1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 102 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…The molecular subtyping of tumors can be used to guide the precision diagnosis and treatment of tumor patients. Cellular and molecular characteristics of tumors have shown potential in precision therapy of PCA, such as cancer-associated fibroblasts (CAFs) and their signature genes [ 12 , 13 ]. Serum prostate-specific antigen (PSA) is the most important marker for PCA; however, it has been criticized for its poor specificity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular subtyping of tumors can be used to guide the precision diagnosis and treatment of tumor patients. Cellular and molecular characteristics of tumors have shown potential in precision therapy of PCA, such as cancer-associated fibroblasts (CAFs) and their signature genes [ 12 , 13 ]. Serum prostate-specific antigen (PSA) is the most important marker for PCA; however, it has been criticized for its poor specificity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts has been reported to be important to many diseases, including cancers [ 8 , 103 108 ]. Our previous study also observed that P4HB was related to cancer-related fibroblasts [ 62 ]. Apart from this kind of stromal cell, we discovered that P4HB had a negative correlation with a range of immune cells in the tumor microenvironment, such as T cells, B cells, and macrophages.…”
Section: Discussionmentioning
confidence: 80%
“…The correlation between P4HB and tumor heterogeneity and stemness related indexes was analyzed and the specific methods could be seen from the previous studies [ 55 62 ]. GSCALite was used to examine the relationship between P4HB and medication sensitivity in pan cancer [ 63 ], which integrated the data of the cancer therapeutics response portal and genomics of drug sensitivity in cancer.…”
Section: Methodsmentioning
confidence: 99%
“…However, the heterogeneity of PCa presents obstacles in both research and clinical management. Previous studies have shown that tumor tissue remodeling and the involvement of cancer-related fibroblasts in recurrence and metastasis underscore the complexity of PCa progression [ 7 , 8 ]. Additionally, both intratumoral and transcriptional heterogeneity may contribute to the evolution of PCa [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%